Uso das técnicas de histerese magnética e ruído magnético de Barkhausen para caracterização microestrutural de aços ferríticos e superferríticos submetidos à degradação térmica - Camelo, Kleyton Jânio (2018)
In this work, magnetic measurements were carried out using vibrating sample magnetometry (VSM), Barkhausen magnetic noise measurements (BMN) and tests of eddy currents. Samples of ferritic (Fe-12Cr-5.5Mo) and superferritic (Fe-25Cr-5.9Mo-5.6Ni) stainless steels were used. The samples were submitted to thermal treatments of solubilization and aging. Conventional techniques of microstructural characterization like optical and scanning electron microscopy and X-ray diffraction. Carbides of the type M(CrMo) 23 C 6 were visualized in the microstructure of the superferritic stainless steel. Evidences of the presence of α’ and Widmanstätten austenite were also found. Rhe formation of χ and σ phases are likely as well. As for the magnetic behavior, the two materials have low coercivity being classified as soft ferromagnetic. The results showed a tendency in increasing the magnetic hardness as a function of the precipitation process of secondary phases in the matrix. Thermal treatments performed at 600 ◦ C caused greater variations in the coercive field of the superferritic steel samples. For the ferritic steel, these variations were more intense in samples treated at 650 ◦ C. This evidence is associated with the intensification of the anchoring process of the domain walls as a consequence of the precipitation of secondary phases, mostly σ phase in the superferritic steel. The remanent magnetization and the saturation magnetization also underwent changes due to the thermal treatments of aging, with increase of the first one and a tendency of reduction in the second one. The BMN was sensitive to changes in microstructure caused by thermal treatments. It was observed that the signal intensity decreases with increasing heat treatment time. This behavior is a direct consequence of the phase precipitation process. Eddy current results showed that the superferritic samples treated at 500 ◦ C were significantly altered indicating possible changes in the microstructure, which resulted in variations in the impedance measurements. The results showed that phase precipitation in steels may be associated with changes in the magnetic properties of these materials. However, it must be considered that the complexity of the microstructure makes it difficult to establish an individual criterion that may cause the change of a specific parameter associated with the magnetization process. The collective effect of the anchoring process of domain walls should be taken into account.